The Relationship of Husband Support with Unmet Need Family Planning in Couples of Childbearing Age - Aqila Fahru Sidqia; Tinuk Esti Handayani; Sunarto; Astuti Setiyani (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Unmet need is a condition where women of reproductive age (WUS) are sexually active but do not use contraception. In 2024, Terung Village recorded an unmet need rate of 11.31%. This condition poses a risk to population control efforts. One contributing factor is the level of husband support. This study aims to analyze the relationship between husband support and unmet need incidence in WUS in Terung Village. The research used an observational, cross-sectional design with 163 respondents selected through simple random sampling. Husband support served as the independent variable, while unmet need was the dependent variable. Data were collected using questionnaires and open interviews, and analyzed using the Chi-Square test.Results showed that 30.1% of WUS experienced unmet need, primarily among women over 35 years old, with elementary education, as housewives, having more than one child, and middle-income status. WUS without husband support had a higher unmet need rate (45.2%) compared to those with full support (10%). The Chi-Square analysis indicated a significant relationship between husband support and unmet need (p = 0.000; α = 0.05). The novelty of this study lies in the considerable disparity in unmet need based on the presence or absence of husband support. Findings emphasize the importance of involving men in family planning decisions, suggesting the need for community-based education to enhance husband participation in contraceptive use.